Good Corporate Governace, Dividend Policy, and Leverage As Determinants Of Earning Management - Ika Sulistyawati, Ardiani; Aprilia Yulianti, Sisi (Inovasi Analisis Data, 2024)
This study aims to examine the impact of Good Corporate Governance, represented by the variables of institutional ownership, managerial ownership, audit committee, independent board of commissioners, dividend policy, and leverage, on earnings management in chemical sub-sector companies on the ISE update in 2020-2023. The results show that the majority of Good Corporate Governance factors have no significant effect, except leverage. The theoretical implications highlight the importance of non-GCG factors in understanding earnings management practices. The benefit is that these results can help companies to better understand what factors really influence earnings management practices, so they can optimize managerial strategies and decision making